LITERATURE REVIEW : PRAKTIK COST RECOVERY DALAM KONTRAK BAGI HASIL (PRODUCTION SHARING CONTRACT) UNTUK SEKTOR MIGAS DI INDONESIA - M. Reza Kurniawan; Adi Perkasa Yudha; Feby Salsabilla; Mozza Ramadhani Putri Evaldi (Lembaran publikasi minyak dan gas bumi, 2026)
This study examines cost recovery practices within the Production Sharing Contract (PSC) scheme and the issues arising from its implementation in Indonesia’s upstream oil and gas sector. The method used is a literature review of scientific articles, government regulations, and institutional reports. The results show that cost recovery plays an important role in encouraging investment by providing cost reimbursement certainty for contractors after commercial production is achieved. Recoverable costs include non-capital, capital, and depreciation costs in accordance with PSC provisions and Government Regulation No. 79 of 2010. However, its implementation faces several challenges, including cost overruns, moral hazard due to misaligned incentives, information asymmetry between contractors and the government, and administrative complexity in audit and verification processes. These findings indicate the need to strengthen governance, improve transparency, and align regulations to ensure the effectiveness of cost recovery and support the optimization of state revenue. This study contributes to the existing literature through an integrative multi-perspective synthesis that consolidates legal, fiscal, and governance dimensions which have previously been studied separately, offering a more comprehensive and structured analytical basis for future policy reform.